2015
DOI: 10.1007/s11095-015-1725-z
|View full text |Cite
|
Sign up to set email alerts
|

Using Environment-Sensitive Fluorescent Probes to Characterize Liquid-Liquid Phase Separation in Supersaturated Solutions of Poorly Water Soluble Compounds

Abstract: Environment-sensitive fluorescence probes are useful to help understand the phase behavior of highly supersaturated aqueous solutions, which in turn is important in the context of developing enabling formulations for poorly soluble compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…The concentrations at where a sharp increase of UV absorption at 700 nm was observed were considered as LLPS onset concentration. 30…”
Section: Solubility and Liquid-liquid Phase Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations at where a sharp increase of UV absorption at 700 nm was observed were considered as LLPS onset concentration. 30…”
Section: Solubility and Liquid-liquid Phase Separationmentioning
confidence: 99%
“…As concluded by multiple reports on this subject, the LLPS phenomenon demonstrate the formation of noncrystalline drug-rich phase occurs under the condition that the critical supersaturation threshold is exceeded. 30,37,38 The HME tablet contains FEN in its amorphous state. In principle, this formulation may yield LLPS provided that a high degree of supersaturation of FEN is encountered.…”
Section: Profiles In Fessif-v2mentioning
confidence: 99%
“…It was suggested that ASD dissolution was governed by a competition between the dissolution rate and the rate of phase separation. 37,38 If APS was initiated immediately when BMS-817399 ASD came in contact to the dissolution medium, the difference between an originally homogeneous ASD and a phase-separated ASD may not be distinguishable by the intrinsic dissolution rate, but this theory cannot explain the decreased polymer release rate after phase separation.…”
Section: The Impact Of Amorphous Phase Separation On the Dissolution mentioning
confidence: 99%
“…6,1720 Colloid formation occurs via a phase-like transition that passes through a critical aggregation concentration (CAC), 2,21,22 akin to a critical micelle concentration (CMC), where liquid colloids rapidly appear. 23 Once formed, the colloids physically sequester proteins, 4 binding them with subnanomolar K d values 2,24 and partially denaturing them. 25 Key aspects of their structure and mechanism have remained elusive, however, owing to their physical properties and instability.…”
mentioning
confidence: 99%